Danger signals in traumatic hemorrhagic shock and new lines for clinical applications - Dufour-Gaume, Frédérique; Frescaline, Nadira; Cardona, Venetia; Prat, Nicolas J. (Frontiers in Physiology, 2023)
Hemorrhage is the leading cause of death in severe trauma injuries. When organs or tissues are subjected to prolonged hypoxia, danger signals—known as damage-associated molecular patterns (DAMPs)—are released into the intercellular environment. The endothelium is both the target and a major provider of DAMPs, which are directly involved in immuno-inflammatory dysregulation and the associated tissue suffering. Although DAMP release begins very early after trauma, this release and its consequences continue beyond the initial treatment. Here we review a few examples of DAMPs to illustrate their pathophysiological roles, with emphasis on emerging therapeutic interventions in the context of severe trauma. Therapeutic intervention administered at precise points during DAMP release may have beneficial effects by calming the inflammatory storm triggered by traumatic hemorrhagic shock.